VOWEL MINIMAL PAIRS IN XITSONGA: PHONOLOGICAL CONTRASTS AND LEXICAL CATEGORISATION WITHIN A STRUCTURALIST - Respect Mlambo; Muzi Matfunjwa (Universitas Islam Sumatera Utara (UISU), 2026)
Research on Xitsonga has not sufficiently examined the role of vowel minimal pairs in distinguishing lexical and grammatical categories, particularly between nouns and verbs. This study investigates how vowel contrasts function phonemically to encode meaning and categorisation in Xitsonga. A data of 25 vowel minimal pairs was collected from dictionaries and scholarly sources, and analysed using morphophonological and thematic approaches within a Structuralist Phonological Theory framework. The findings reveal that vowel contrasts play a systematic role in lexical differentiation, occurring across initial, medial, and final positions, as well as cross-category contrasts between nouns and verbs. Initial vowel contrasts differentiate verbs, medial contrasts exist in both nouns and verbs, and final vowel contrasts occur in nouns. Cross-category contrasts further underscore the role of vowels in marking lexical category distinctions, revealing systematic positional regularities within the language’s phonological system. These patterns demonstrate that vowel quality functions as a structural marker of meaning and lexical categorisation in Xitsonga. This study contributes to Xitsonga phonology by providing a systematic account of vowel minimal pairs and their grammatical significance. It also offers empirical support for structuralist principles by showing how phonemic opposition operates in Xitsonga, with implications for phonological theory, language documentation, and pedagogy.